2022
DOI: 10.1051/kmae/2022003
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerability of British aquatic insects to climate change

Abstract: Freshwater ecosystems are particularly at risk from climate change due to the intrinsic link between the physical properties of the water environment and those species that live there. Mayflies, stoneflies and caddisflies are key indicators of the health of freshwater environments and their biological traits and ecological preferences determine their vulnerability to climate change. Traits and preferences for 289 British species were analysed, with voltinism, length of flight period, altitudinal preference and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Perhaps the main reason is that most protected areas have been established primarily to protect vertebrates and plants in terrestrial ecosystems. However, freshwater ecosystems are among the most threatened ecosystems in terms of biodiversity loss [3,72], especially with respect to sensitive aquatic insect orders [64,73,74], and they support 9.5% of all described animal species [75]. Based on our models, H. bacescui will lose approximately one-to two-thirds of its range depending on climate model implementation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Perhaps the main reason is that most protected areas have been established primarily to protect vertebrates and plants in terrestrial ecosystems. However, freshwater ecosystems are among the most threatened ecosystems in terms of biodiversity loss [3,72], especially with respect to sensitive aquatic insect orders [64,73,74], and they support 9.5% of all described animal species [75]. Based on our models, H. bacescui will lose approximately one-to two-thirds of its range depending on climate model implementation.…”
Section: Discussionmentioning
confidence: 87%
“…This is highly important from the perspective of habitats preferred by H. bacescui, as small streams and brooks may be affected by high air temperatures due to the close relationship between water and air temperatures [8]. In the study concerning the vulnerability of British aquatic insects, it was concluded that caddisfly species found in small lowland streams are at risk from climate change [64].…”
Section: Discussionmentioning
confidence: 99%
“…A projected warming of >1.28°C was associated with end of the century assemblages that either had: (i) increased occurrence of Mollusca, Crustacea and Oligochaeta, but generally fewer insect groups than baseline; or (ii) increased occurrence of Odonata, Chironomidae (Diptera) and Baetidae (Ephemeroptera) insect species, but fewer Plecoptera and Ephemeroptera (except for Baetidae) and Coleoptera species than baseline. These shifts in community composition are explicable, in part, in terms of taxonomic differences in thermal tolerances (Macadam et al., 2022). Plecoptera and Ephemeroptera have lower upper thermal tolerances than other taxa, especially Mollusca (Stewart et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of impacted sites should seek to enhance biodiversity by regenerating woodland and increasing hydrological habitat heterogeneity. Such restoration could also promote ecological resilience to climate change – a pressure to which species in headwater springs and streams are particularly vulnerable (Macadam et al, 2022).…”
Section: Discussionmentioning
confidence: 99%